PEMBANGUNAN DERMAGA SUNGAI TAYAN KABUPATEN SANGGAU DENGAN MEMPERTIMBANGKAN MUKA AIR TERTINGGI SERTA TERENDAH - Hawinuti, Riska; Suprianus, Suprianus (Lambung Mangkurat University Press, 2023)
The Tayan River dock is a river port that supports the loading and unloading of passengers and goods via the river route, with purpose to improving the standard of living and economy of the community. The condition of the dock during the initial survey required physical improvement and enhancement of the dock and its supporting facilities. The aim of this article is to review the work of the dock on the elevation position above the dock (EAD) and the highest and lowest water levels for each type of dock. The method used is a direct observation of the physical work of loading and unloading docks, dolphin docks, and sampan docks. Based on EAD and water level conditions, it is planned for a maximum of 1.000 Dead Weight Tonnage (DWT) ships at the loading and unloading docks and dolphin docks; and a maximum of 7 DWT for sampan docks. The elevation for loading and unloading docks: EAD +100,017 meters Above Sea Level (MSL); highest water level +99,670 MSL; normal high tide +98,017 MSL and normal water level +95,517 MSL. For dolphin docks: EAD +97,170 MSL; normal water level +91,517 MSL and low water level +88,267 MSL. And for sampan docks: EAD +97,170 MSL; normal water level +91,517 MSL and lowest water level +88,267 MSL. The riverbed depth is +81,527 MSL with the lowest water level +88,267 MSL, which can still be used by ships with a draft < 6,74 M, making it safe for ships during the lowest water level.